Empirical study of the professional empathy of future rescuers - Olena Stepanivna Vavryniv (Insight: the psychological dimensions of society, 2020)
The article analyzes the main views on the problemof working in special conditions and the peculiaritiesof the development of professional empathyof future rescuers. The purpose of the empiricalresearch is to establish individual psychologicalcorrelatives of professional empathy of future rescuers.Methods: theoretical analysis and generalization;Freiburg multifactor personal questionnaire“FPI”; “Diagnosis of emotional intelligence”(N. Hall); “Balanced Emotional Empathy Scale -BEES”, A. Mehrabian – a modification of N. Epstein;“Diagnosis of the level of empathic abilities” V. Boiko;“Motivation for success” by T. Ehlers and “Diagnosisfor motivation to avoid failures” by T. Ehlers; “SACS”(S. Hobfoll, adapted by N. Vodopyanova and O. Starchenkova);“Forecast” (assessment of neuropsychiatricinstability); “Diagnosis of the risk readinesslevel” A. Schubert. Results. The social psychologicalfeatures of the formation of professional empathyare described and the definition of the conceptof “professional empathy of the rescuer” is given. It has been found that the study participants havea high level of empathy, high level of risk readiness,high level of motivation for success, mediumlevel of motivation to avoid failure, high levelof neuropsychiatric stability, high and medium levelof spatial representations’ ability to establish socialcontact, ability to control their emotions, self-motivation,sociability, balance, extroversion, opennessand masculinity. Empathy correlates have also beenestablished. High levels of empathy are closely correlatedwith indicators such as attitudes that promoteor hinder empathy, penetrating empathy, riskreadiness, high levels of motivation for success,sociability, masculinity, assertive actions, emotionalawareness, high levels of neuropsychiatric stability,a moderately high level of motivation to avoid failure.Conclusions. Correlation analysis has foundthat empathy is positively influenced by education,namely the development of motivation to help others.The ability to empathize will promote positiveadaptation in society and the establishment of socialcontacts. Cadets with a low level of empathy areaggressive and prone to cruelty, they do not seek toavoid failure or have certain internal fears.